Analyzing the effects of uncertainties on the economic performance of a chemical process plant using a probabilistic optimization technique - Woldetensay, Mesfin; Mahadzir, S.; Lee, M. (Elsevier, 2012)
This work presents a mathematical optimization model based on a probabilistic approach to clearly identify the effects material flow uncertainties, from both plant inlet and outlet, on the overall economic performance of a plant. Accordingly, two case studies have been taken for an existing gas processing plant. Each profit analysis for the case studies is made with respect to the reliability of holding the process constraints. Based on this, a user-defined probability or confidence level has been assigned for the constraints between the ranges of 50% to 100%. There is a significant profit change of more than 85.8 % for the plant inlet uncertainty case as the confidence level increase from 96% to 100%. However, the profit change for uncertainty from the plant outlet is much less (1.93%) compared to that of the plant inlet for the same confidence level interval taken. The result indicates that much emphasis should be given to those uncertainties from the plant inlet which has a major effect in the overall economic performance of the plant performance.